Extramedullary Plasmacytoma of the Tonsil - Kevin C. Huoh; Annemieke Van Zante; David W. Eisele (Case Reports in Otolaryngology)
Plasma cell tumors are a diverse group of neoplasms characterized by monoclonal proliferation of plasma cells. Extramedullary plasmacytoma (EMP) is a rare form of localized plasma cell tumor that arises most often in the head and neck region. We present an unusual case of EMP of the palatine tonsil from a tertiary care university hospital. We discuss the histopathologic and radiologic evaluation as well as treatment of EMP.